Picard–Lefschetz theory and dilating ℂ*‐actions. (2nd November 2015) - Seidel, Paul
Abstract : We considerC * ‐actions on Fukaya categories of exact symplectic manifolds. Such actions can be constructed by dimensional induction, going from the fibre of a Lefschetz fibration to its total space. We explore applications to the topology of Lagrangian submanifolds, with an emphasis on ease of computation.